Effect of Injection Molding Melt Temperatures on PLGA Craniofacial Plate Properties during In Vitro Degradation - Melo, Liliane Pimenta de; Salmoria, Gean Vitor; Fancello, Eduardo Alberto; Roesler, Carlos Rodrigo de Mello (International Journal of Biomaterials, 2017)
The purpose of this article is to present mechanical and physicochemical properties during in vitro degradation of PLGA material as craniofacial plates based on different values of injection molded temperatures. Injection molded plates were submitted to in vitro degradation in a thermostat bath at 37 ± 1°C by 16 weeks. The material was removed after 15, 30, 60, and 120 days; then bending stiffness, crystallinity, molecular weights, and viscoelasticity were studied. A significant decrease of molecular weight and mechanical properties over time and a difference in FT-IR after 60 days showed faster degradation of the material in the geometry studied. DSC analysis confirmed that the crystallization occurred, especially in higher melt temperature condition. DMA analysis suggests a greater contribution of the viscous component of higher temperature than lower temperature in thermomechanical behavior. The results suggest that physical-mechanical properties of PLGA plates among degradation differ per injection molding temperatures.